Non-stop mRNA decay: a special attribute of trans-translation mediated ribosome rescue - Venkataraman, Krithika; Guja, kip; Garcia-Diaz, Miguel; Karzai, Wali (Frontiers in Microbiology, 2014)
Decoding of aberrant mRNAs leads to unproductive ribosome stalling and sequestration of components of the translation machinery. Bacteria have evolved three seemingly independent pathways to resolve stalled translation complexes. The trans-translation process, orchestrated by the hybrid transfer-messenger RNA (tmRNA) and its essential protein co-factor, small protein B (SmpB), is the principal translation quality control system for rescuing unproductively stalled ribosomes. Two specialized alternative rescue pathways, coordinated by ArfA and ArfB, have been recently discovered. The SmpB-tmRNA mediated trans-translation pathway, in addition to re-mobilizing stalled translation complexes, co-translationally appends a degradation tag to the associated nascent polypeptides, marking them for proteolysis by various cellular proteases. Another unique feature of trans-translation, not shared by the alternative rescue pathways, is the facility to recruit ribonuclease R (RNase R) for targeted degradation of non-stop mRNAs, thus preventing further futile cycles of translation. The distinct C-terminal lysine-rich (K-rich) domain of RNase R is essential for its recruitment to stalled ribosomes. To gain new insights into the structure and function of RNase R, we investigated its global architecture, the spatial arrangement of its distinct domains, and the identities of key functional residues in its unique K-rich domain. Small-angle X-ray scattering models of RNase R reveal a tri-lobed structure with flexible N- and C-terminal domains, and suggest intimate contacts between the K-rich domain and the catalytic core of the enzyme. Alanine-scanning mutagenesis of the K-rich domain, in the region spanning residues 735 and 750, has uncovered the precise amino acid determinants required for the productive engagement of RNase R on tmRNA-rescued ribosomes. Theses analyses demonstrate that alanine substitution of conserved residues E740 and K741result in profound defects, not only in the recruitment of RNase R to rescued ribosomes but also in the targeted decay of non-stop mRNAs. Additionally, an RNase R variant with alanine substitution at residues K749 and K750 exhibits extensive defects in ribosome enrichment and non-stop mRNA decay. In contrast, alanine substitution of additional conserved residues in this region has no effect on the known functions of RNase R. In vitro RNA degradation assays demonstrate that the consequential substitutions (RNase RE740A/K741A and RNase RK749A/K750A) do not affect the ability of the enzyme to degrade structured RNAs, indicating that the observed defect is specific to the trans-translation related activities of RNase R. Taken together, these findings shed new light on the global architecture of RNase R and provide new details of how this versatile RNase effectuates non-stop mRNA decay on tmRNA-rescued ribosomes.